Chapter 48: Migrant homemaking in Sub-Saharan Africa: from self-help housing to conspicuous construction - Pauli, Julia (Edward Elgar Publishing, 2023)
Massive displacements, forced labor migration, and large-scale resettlements ordered by colonial states, but also internal and transnational migration, have stimulated specific forms of homemaking in urban and rural regions throughout sub-Saharan Africa. The chapter first briefly scrutinizes earlier forms of housebuilding and migration in colonial African contexts that let to various forms of self-help housing and the appropriation of colonial urban planning and state housing. Extending on these insights, conspicuous house constructions by regional elites and, increasingly, by the so-called emergent African middle classes, are discussed. A third section describes transnational migrants and their homemaking practices. Finally, it is argued that these three phenomena - self-help housing, elite/middle-class housing, and transnational home constructions - are not separate phenomena but have to be understood within the complex webs of kin relations in which they are embedded.